Socialization of making moringa pudding to increase HB levels for pregnant women with anemia - Hasnita; Uliarta Marbun; Irnawati (Abdimas Polsaka, 2025)
Anemia remains a significant public health concern among pregnant women, with increased risks of complications during pregnancy, low birth weight, and maternal mortality. Pregnant women require twice as much iron as non-pregnant women, making adequate iron intake essential. Moringa (Moringa oleifera) leaves, rich in iron and essential nutrients, can potentially improve haemoglobin (Hb) levels. This community service program aimed to provide education on the benefits of moringa leaves and to demonstrate the preparation of nutrient-rich moringa pudding as a healthy, locally sourced alternative to prevent anaemia in pregnant women. The activity was conducted at Pattingaloang Public Health Centre, involving 13 pregnant women. The implementation included lectures, leaflets, discussions, and demonstrations of moringa pudding preparation. Pre- and post-tests were used to measure participants’ knowledge. Results showed an increase in the proportion of participants with sound knowledge from 77% before the intervention to 100% afterwards. The active participation and enthusiasm of the attendees indicated high acceptance of the intervention. This initiative improved knowledge and skills in utilising moringa leaves for nutritional enhancement during pregnancy. It also encouraged community empowerment by promoting local food processing innovations. Sustained implementation of such programs can potentially reduce anemia prevalence and improve maternal health outcomes